EDUKASI RESIKO PENGGUNAAN PUPUK CAIR PADA EKOSISTEM BUDIDAYA RUMPUT LAUT DI DESA KOJA DOI, SIKKA, MAUMERE - Qoriasmadillah, Wanda; Ilhami, Baiq Tri Khairina; Haqiqi, Nirwana; Prasedya, Eka Sunarwidhi; Widyastuti, Sri (Jurnal Abdi Insani, 2024)
Seaweed cultivation is one of the superior aquatic commodities in East Nusa Tenggara (NTT) Province. In Sikka Regency, the majority of coastal communities work as seaweed cultivators. There are several efforts made by the community to increase seaweed production, one of which is by using Green Tonik (GT) liquid fertilizer. However, the use of GT fertilizer can cause macronutrient accumulation in the sea. This accumulation causes the bloom of unwanted microorganisms, thus damaging the stability of the marine ecosystem. The aim of this service activity is to hope that the people of Koja Doi, Sikka Regency, Maumere understand the impacts and risks of using GT liquid fertilizer so that it is not reused in seaweed cultivation or other cultivation in the future. The method used in this service is direct education and outreach by visiting the homes of several seaweed farmers who are affected by the use of GT liquid fertilizer. Apart from that, a discussion session was held between the service team and the community as a step to exchange information. The result of this activity was that information was obtained that the use of GT liquid fertilizer was initiated by the community based on the use of GT fertilizer on land which was able to increase crop production. As a result of the use of this fertilizer, no cultivated seaweed can live in these waters. Scientific research has not been carried out regarding the levels of macronutrient content found in Koja Doi waters so the current consequences are only based on assumptions from the community. Through this research, the community understands the impacts and risks of using GT liquid fertilizer so that people will not use the same or different liquid fertilizer in seaweed cultivation in the future.